2021
DOI: 10.1177/2050640620966513
|View full text |Cite
|
Sign up to set email alerts
|

Time trends in incidence and prevalence of chronic pancreatitis: A 25‐year population‐based nationwide study

Abstract: Background Updated population-based estimates on incidence and prevalence of chronic pancreatitis are scarce. Methods We used nationwide healthcare registries to identify all Danish patients diagnosed with chronic pancreatitis and computed crude and standardised incidence rates and prevalence estimates in 1994–2018. Incidence and prevalence were evaluated in relation to patients age and gender, aetiology (alcoholic vs non-alcoholic) and smoking and alcohol consumption in the general Danish population. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 37 publications
1
22
1
1
Order By: Relevance
“…Prevalence of CP in Europe is shown to be between 16 and 154 per 100,000 ( 11 , 39 , 40 ). A recent study showed the prevalence of CP in the United States to be 73 per 100,000 with a peak of 135 per 100,000 for the 46–55-year age group ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of CP in Europe is shown to be between 16 and 154 per 100,000 ( 11 , 39 , 40 ). A recent study showed the prevalence of CP in the United States to be 73 per 100,000 with a peak of 135 per 100,000 for the 46–55-year age group ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic analysis in 195 countries and territories revealed that the age-standardized prevalence and years lived with disability of overall pancreatitis increased between 1990 and 2017 3 . Therein, the evidence on an increasing trend of CP prevalence was also observed in several countries 4 , 5 . Thus, CP has become a critical public health problem.…”
Section: Introductionmentioning
confidence: 62%
“…Moreover, CP is also associated with pancreatic cancer with more than an 8-fold increased probability of tumour development [2]. Epidemiological data have shown an increased incidence of CP in recent years [3,4]. Considering the high disease morbidity and mortality, clinicians should be aware of the risk factors responsible for the onset of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…60-day-old male C57BL6/ cmdb mice (a strain developed in CEM) were subjected to a 12-h dark/light cycle at 22 °C, with free access to water and standard rodent chow ad libitum. We decided to use males because the incidence and prevalence of CP in humans is twice as common in men than in women [3,19]; moreover, cigarette addiction is more common in men.…”
Section: Introductionmentioning
confidence: 99%